Verticulture of Lettuce (Lactuca sativa L.) in the Growick Irrigation System with Various Wick Widths - Mellisa Mellisa; Ismed Inonu; Herry Marta Saputra (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2023)
The growick irrigation system is an underground irrigation that can prevent plant water loss because it directly wets the root area. The use of the width of the wick in the growick irrigation system is can meet the water needs of the growing media. The aimed of this study were to determine the effect of wick width using the growick irrigation system on the growth and yield of lettuce grown vertically. This research was conducted from April to May 2021. The research location was in the Experimental and Research Station, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung. The study was conducted using a randomized block design experimental method (RBD) which consisted of 5 levels of treatment. The treatment consisted of control, wick width 0.5, 1, 1.5, 2 cm. The result shows that width of the wick of the growick and verticulture irrigation systems affected the crop water consumption but had no significant effect on the growth parameters and yield of lettuce. The treatment of 0,5 cm wick width tends to be better in supporting the growth and yield of lettuce in the vertical cultivation systems.